Post-Fire Hazard and Risk Assessment in Fire-Affected Areas with GIS and Satellite Imagery: The Case of 2015 Laconia Forest Fire (Southeastern Peloponnese, Greece) - Lekkas, E.; Filis, C; Andreadakis, E.; Skourtsos, E.; Diakakis, M.; Mavroulis, S.; Papaspyropoulos, K.; Alexoudi, V.; Kommatas, M.; Karalemas, N.; Vassilakis, Emm.; Milios, D.; et al. (Safe Greece - Safe Evros 2016, 2016)
On July 17, 2015 a forest fire that broke out in the southern part of Epidavros Limira peninsula (Laconia, southeastern Peloponnese), expanded rapidly due to strong winds blowing in the area and raged out of control for two days, inducing substantial damage to agriculture, livestock farming, buildings and infrastructure and causing one fatality. Innovative GIS-based methods were developed and implemented for the first time in a fire-affected area in Greece for mapping the post-fire erosion, flood and landslide hazards and risks. Geomorphological, geological, tectonic, hydrological, meteorological and land-use data along with a WorldView-2 satellite image and post-fire field observations were evaluated and used. A newly developed method was applied for assessing the erosion hazard. Analytic Hierarchy Process and Weighted Linear Combination methods were used for assessing the post-fire landslide susceptibility. The HEC-RAS model was used for hydraulic simulation and assessment of flood risk under post-fire conditions. Post-fire erosion, flood and landslide hazard and risk maps were constructed for the affected area delineating locations with very low, low, moderate, high or very high hazard and risk of erosion, flood and landslide respectively. The developed methodology is a useful post-fire hazard and risk assessment tool and can be applied by state authorities to assess the geo-environmental impact of fire disasters in areas with similar environmental conditions.